Electric bus system with rapid charging at every bus stop using renewable energy - Takeshi KAWASHIMA (The Japan Society of Mechanical Engineers, 2014)
In order to prevent global warming, the emissions of greenhouse gases must be reduced. In public transportation systems, electric buses can help to achieve this. However, the deployment of electric buses has been limited to public corporations as a result of the weight of the required energy storage devices. One approach to addressing this problem is rapidly charging the electric bus at every bus stop, thereby reducing the required energy storage and weight. In addition, charging buses using electrical power generated from renewable energy sources could further reduce emissions of greenhouse gases. For such a system, the required energy for each bus route must be estimated and the storage device designed to minimize the weight of the bus. In this study, the feasibility of the proposed system is confirmed by a demonstration experiment using a converted electric minivan. Then, a simulator to calculate the energy consumption of a full-size bus is developed by extrapolating the parameters used in a simulator for the electric minivan, which were validated experimentally. A trial bus-mounted storage device for the route is also designed.